ISLAM WASATHIYAH TO BUILD A DIGNIFIED INDONESIA - Tambunan, Amirsyah (ADI Journal on Recent Innovation (AJRI), 2019)
Muslims in Indonesia in Indonesia face global challenges in the form of liberalism in various dimensions of life. Therefore, Muslims can express their aspirations through the known 411 action, 212 in a peaceful manner. Various parties respect Muslims, because they are able to prove Muslims who agree in Indonesia. Carrying out Islam wasathiyah (moderate), so as not to cause anarchy. However important prevention efforts that promote Islam as a religion of mercy to all the worlds (Islam rahmata lil 'alamin) through understanding of Islam washatiyah, to avoid understanding the extreme form of terrorism, anarchism, separatism and other forms of destructive life of society, nation and state.